2015
DOI: 10.4236/health.2015.714201
|View full text |Cite
|
Sign up to set email alerts
|

Put Yourself in My Shoes: Perspectives of Adolescents about What Makes an Obesity Intervention Effective

Abstract: Purpose: This study aims to investigate the adolescents' perspectives about 1) the changing process promoted by a weight management program; 2) the factors which may act as facilitators and barriers to obesity management; 3) the strategies that should be included in order to design a successful weight management program. Methods: Data were collected by in-depth interviews and focus group discussions with 16 overweight adolescents, aged 12-18 years. Thematic analysis was used for analysing the data. Results: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…These dynamics are a major challenge for clinical practice and for research. Our data support other studies, suggesting the relevance of the family as a crucial context for the promotion of healthy lifestyles and highlighting the impact that moving the focus of the intervention from the adolescent to the family may have (30).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These dynamics are a major challenge for clinical practice and for research. Our data support other studies, suggesting the relevance of the family as a crucial context for the promotion of healthy lifestyles and highlighting the impact that moving the focus of the intervention from the adolescent to the family may have (30).…”
Section: Discussionsupporting
confidence: 89%
“…Our data support other studies, suggesting the relevance of the family as a crucial context for the promotion of healthy lifestyles and highlighting the impact that moving the focus of the intervention from the adolescent to the family may have (30). These dynamics are a major challenge for clinical practice and for research.…”
Section: Discussionsupporting
confidence: 85%
“…Although these variables are secondary outcomes, they have been pointed out as most influential on weight management. For example, a recent qualitative study [ 20 ] identified positivity, i.e., the generation of positive emotions, as a relevant feature of a ICT effective weight management program.…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction with the intervention is based on: the focus of and activities in the programme (Barlow & Ohlemeyer, 2006), the relationship with the coaches and other participants (Prioste, Fonseca, Sousa, Gaspar, & Francisco, 2015;Smith et al, 2014) and whether expectations are met (Sallinen et al, 2013). A lack of trust or connection with coaches and participants or disliking activities or the group dynamics may be barriers to adherence (Nobles et al, 2016).…”
Section: Stage 3: Adherencementioning
confidence: 99%